Traceability of animal meals in Japanese quail eggs using the technique of 13C e 15N* stable isotopes - Mori, C [UNESP]; Ducatti, C [UNESP]; Pizzolante, CC; Kakimoto, SK; Denadai, JC (Fundação APINCO de Ciência e Tecnologia Avícolas, 2013)
The objective of this study was to trace the inclusion of bovine meat and bone meal (BMBM) in the diet of Japanese quails by analyzing eggs and egg fractions (yolk and albumen) by the technique of carbon-13 (13C) and nitrogen-15 (15N) stable isotopes. In the trial, 120 Japanese quails were distributed in six treatments with four replicates of five birds each. The following treatments were applied: feed based on corn and soybean meal, containing graded BMBM inclusions (0, 1, 2, 3, 4 or 5%). After 42 days, 20 eggs per treatment were randomly collected for three consecutive days. Ten eggs were used for yolk and albumen sample collection, and ten for total egg sample collection. It was possible to detect the dietary inclusion of 1% BMBM in the egg and its fractions. Therefore, the technique of isotopes 13C and 15N is able of tracing since 1% inclusion level of BMBM in the diet of Japanese quails in eggs and their fractions.
Keywords: Carbon-13; Coturnix coturnix japonica; bovine meat and bone meal; certification; nitrogen-15